Pengaruh Kemasan, Variasi Produk dan Citra Merek terhadap Keputusan Pembelian Susu Cair dalam Kemasan Kotak 250 ML Indomilk di Alfamart Pondok Indah 2 - Fidriyanti, Amelia; Putra, Suadi Sapta; Digdowiseiso, Kumba (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aim to analyze the effect of packaging, product variation and brand image on purchasing decisions for 250ml Indomilk packaged liquid milk at Alfamart Pondok Indah 2. This study uses primary data with data collection methods through a questionnaire distributed to 96 respondent. Data analysis technique uses inferential with multiple linear regression and using Statistical Product and Service Solution (SPSS) version 23.0 program. From the result of multiple linear regression analysis, it shows that the packaging variable (X1), the product variation variable (X2), and the brand image variable (X3) has a positive and significant influence on the dependent variable purchasing decisions of 250 ml Indomilk packaged liquid milk at Alfamart Pondok Indah 2.